RETRACTED: A Ferulic Acid Derivative FXS-3 Inhibits Proliferation and Metastasis of Human Lung Cancer A549 Cells via Positive JNK Signaling Pathway and Negative ERK/p38, AKT/mTOR and MEK/ERK Signaling Pathways - Shi-Jun Yue; Peng-Xuan Zhang; Yue Zhu; Nian-Guang Li; Yan-Yan Chen; Jia-Jia Li; Sai Zhang; Ru-Yi Jin; Hao Yan; Xu-Qin Shi; Yu-Ping Tang; Jin-Ao Duan (Molecules)
Lung cancer is one of the most common malignancies and is an increasing cause of cancer-related deaths. In our previous study, a series of ferulic acid (FA) derivatives were designed and synthesized; they exhibited positive anti-cancer activities, especially for a compound labelled FXS-3. In this study, a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was performed, wherein it revealed the inhibitory effect of FXS-3 on the proliferation and metastasis of human lung cancer A549 cells. The further flow cytometry assay showed that FXS-3 induced apoptosis of A549 cells induced cell cycle arrest at the G0/G1 phase. The trans-well migration and Matrigel invasion assays revealed that FXS-3 inhibited the migration and invasion of A549 cells. By the western blotting analysis, FXS-3 increased the expression of B-cell lymphoma-2 (Bcl-2) associated X protein (Bax)/Bcl-2 ratio, inhibited matrix metalloproteinase (MMP)-2 and MMP-9, and regulated the extracellular signal-regulated kinase (ERK)/p38, c-Jun N-terminal kinase (JNK), protein kinase B (AKT)/mechanistic target of rapamycin (mTOR), as well as mitogen-activated protein kinase (MEK)/ERK signaling pathways. The subsequent A549 xenograft-bearing mouse model and tail vein injection of A549 cells induced pulmonary tumor metastasis model showed that FXS-3 significantly restrained the tumor growth and metastasis. In conclusion, FXS-3 might inhibit proliferation and metastasis of human lung cancer A549 cells by positively regulating JNK signaling pathway and negativly regulating ERK/p38, AKT/mTOR, and MEK/ERK signaling pathways, which provides important scientific basis for the development of anti-cancer drugs about FA derivatives.